2020
DOI: 10.1038/s41598-020-57686-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of silver-based additives for the development of antibacterial functionality in Laser Sintered polyamide 12 parts

Abstract: Infectious diseases (exacerbated by antimicrobial resistance) cause death, loss of quality of life and economic burden globally. Materials with inherent antimicrobial properties offer the potential to reduce the spread of infection through transfer via surfaces or solutions, or to directly reduce microbial numbers in a host if used as implants. Additive Manufacturing (AM) techniques offer shorter supply chains, faster delivery, mass customisation and reduced unit costs, as well as highly complicated part geome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 27 publications
(22 reference statements)
1
35
0
Order By: Relevance
“…13 The areas of loose powder that are not scanned during a print act as supports for any overhanging areas of the print allowing complex geometries to be created with less waste of materials in the generation of supports. 14 Both SLA and SLS, require post print processing steps that creates the need for additional materials and equipment, which can be a disadvantage during a pandemic environment as products needed to be created rapidly, within a short period of time. Moreover, potential toxicity issues in SLA printed parts need also to be considered, as can be caused by leaching of photoinitiator residues, which are prominently cytotoxic, and in some other cases due to incomplete printing or post-curing items.…”
Section: D-printed Objects and Antimicrobial Activitymentioning
confidence: 99%
“…13 The areas of loose powder that are not scanned during a print act as supports for any overhanging areas of the print allowing complex geometries to be created with less waste of materials in the generation of supports. 14 Both SLA and SLS, require post print processing steps that creates the need for additional materials and equipment, which can be a disadvantage during a pandemic environment as products needed to be created rapidly, within a short period of time. Moreover, potential toxicity issues in SLA printed parts need also to be considered, as can be caused by leaching of photoinitiator residues, which are prominently cytotoxic, and in some other cases due to incomplete printing or post-curing items.…”
Section: D-printed Objects and Antimicrobial Activitymentioning
confidence: 99%
“…This tactic can be further explored in other implants to elute antibiotics post-implantation. Apart from post-processing step to equip the final product with antibacterial and microbial agents, the product itself can be made of metals (such as silver, copper, and zinc) which possess biocidal properties (Turner et al 2020). Scientists have also explored in situ functionalization while manufacturing, by adding fillers to the main material.…”
Section: Surface Functionalization On Am Parts With Antibacterial Effectmentioning
confidence: 99%
“…This process is repeated until the intended model is completed (Paul and Anand, 2012;Valino et al, 2019). For this approach, addition of powder M/MO nanoparticles with the polymer powder is done by mechanical mixers such as rotary tumblers (Turner et al, 2020). The mixing process is easier and can result in a more uniform distribution of nanoparticles when compared to FDM.…”
Section: D Printing Of Thermoplastic Nanocompositesmentioning
confidence: 99%
“…They also tested these nanocomposites with real patients and demonstrated that this manufacturing approach is a promising treatment option for patients diagnosed with complete edentulism (Totu et al, 2017;Cristache et al, 2020). Turner et al (2020) introduced a SLS printing of antibacterial nanocomposite by mixing polyamide 12 with 1% of commercially available B65003 silver additives to make delicate, complex, and personalized devices for medical and healthcare applications (Turner et al, 2020).…”
Section: Applicationsmentioning
confidence: 99%